Sodium butyrate supresses malignant human mast cell proliferation, downregulates expression of KIT and promotes differentiation - MacDonald, Clayton A.; Qian, Hui; Pundir, Priyanka; Kulka, Marianna (Frontiers in Allergy, 2023)
Sodium butyrate (NaBu) is a class I histone deacetylase inhibitor (HDACi) that can impede the proliferation of transformed cells. Although some HDACi downregulate the expression of the stem cell factor receptor (KIT/CD117), the effect of NaBu on KIT expression and human mast cell proliferation requires further elucidation. In this study, we examined the effects of NaBu on three transformed human mast cell lines, HMC-1.1, HMC-1.2 and LAD2. NaBu (100 M) inhibited the proliferation and metabolic activity of all three cell lines without significantly affecting their viability, suggesting that although the cells had ceased to divide, they were not yet undergoing apoptosis. Cell cycle analysis using the cell-permeant dye, propidium iodide, indicated that NaBu significantly blocked the cell cycle progression of HMC-1.1 and HMC-1.2 from G1 to G2+M phases. Furthermore, NaBu downregulated the expression of C-KIT mRNA and KIT protein expression in all three cell lines, but this effect was most significant in the HMC-1.1 and HMC-1.2, both of which harbour activating mutations in KIT, which proliferate more rapidly than LAD2. These data support earlier observations showing that human mast cell lines are sensitive to histone deacetylase inhibition. However, our data presents the novel observation that inhibition of cell proliferation by NaBu was not associated with a loss in cell viability but rather an arrest of the cell cycle. Higher concentrations of NaBu led to modest increases in histamine content, tryptase expression, and granularity. In conclusion, NaBu treatment of human mast cell lines led to a modest enhancement of the hallmarks of mature mast cells.